Nanoscale semiconductor memories : technology and applications - Kurinec, Santosh K.; Iniewski, Krzysztof (Devices, circuits, and systems)
"Preface At no time in the history of the semiconductor industry has memory technology assumed such a pivotal position. The last decade has seen a remarkable shift in usage and value of semiconductor memory technologies. These changes have been driven by the elevation of three particular target applications for the development of memory technology performance attributes. The first and most obvious shift is that mobile multimedia applications such as tablets and advanced cell phones have now replaced desktop data processing as the primary target for many new semiconductor technologies. The significance of this shift is that the smaller form factor and smaller semiconductor content automatically increases the percentage of value contributed by the analog wireless and the memory components. The second trend is driven by the explosive growth in the sheer volume of data that is being created and stored. The continuing growth in digital information is heavily driven by mobile multimedia access to cloud storage on the Internet as well as the astounding increase in image data storage and manipulation. The third trend is the shift of emphasis from the individual components to the ability to configure some high-volume elements in subsystems and multidie packages rather than as discrete components on a motherboard. Over the past three decades, numerous memory technologies have been brought to market with varying degrees of commercial success, such as static random-access memory (SRAM), pseudostatic RAM, NOR flash, erasable programmable readonly memory (EPROM), electrically erasable programmable read-only memory (EEPROM), dynamic RAM (DRAM), and NAND flash. Generally speaking, these "memory" technologies can be split into two categories: volatile and nonvolatile"--